Investigating the impact of foreign direct investment on NTEs and imports in Zambia - Kapota, Derby Bwalya (Research of GSB, 2017)
The need for foreign direct investment in Zambia emanated from the country's search for finance to support the diversification agenda backed by the private sector. Sectors that will see a diversified export earning capacity were identified as target areas for foreign direct investment. The expectation from such investments was that the country will see improved production capacities leading to the increase of NTEs and production of products that could only be accessed through the foreign markets. This research therefore aimed at investigating the impact of FDIs on NTEs and imports by category. This is on the theoretical backdrop of both the modernisation and dependency theories which highlights that the effects of FDI on the host country could either be negative or positive. The research looked at time series data for NTEs and imports by category for the period 1994 to 2014. A simple Ordinary least squares regression was used. Besides FDIs, two other variables namely trade openness and real effective exchange rate index were included in the study. The results indicate that FDI have a positive effect on both NTEs and all the four categories of imports. The magnitude of the impact on NTEs was as high as that of imports in all the four categories. The implication is that much as FDI can be said to contribute to the increased NTEs, its impact on imports are equally the same and therefore has not necessarily improved the countries overall trade performance during the periods under consideration.